Modulation of O‐antigen chain length by the wzz gene in Escherichia coli O157 influences its sensitivities to serum complement. (16th September 2013) - Osawa, Kayo; Shigemura, Katsumi; Iguchi, Atsushi; Shirai, Hiroki; Imayama, Toru; Seto, Kazuko; Raharjo, Dadik; Fujisawa, Masato; Osawa, Ro; Shirakawa, Toshiro
ABSTRACT Escherichia coli O157 strains belonging to a distinct lineage and expressing different O‐antigen (Oag) lengths were isolated. Although the function of wzz in E. coli has not been adequately investigated, this gene is known to be associated with regulation of Oag length. Using E. coli O157:H7 ATCC43888 (wild‐type), several wzz mutants of E. coli O157, including a wzz deletion mutant, were generated and the relationship between the length of Oag modulated by the wzz gene and sensitivities to serum complement investigated. SDS–PAGE, immunoblot analyses and sensitivity tests to human serum complement were performed on these strains. The lengths of the O157‐antigen could be modulated by the wzz gene mutations and were classified into long, intermediate and short groups. The short chain mutant was more serum sensitive than the wild‐type strain and the other wzz mutants (P < 0.001). In conclusion, Oag chain length modulated by the wzz gene in E. coli O157 influences its sensitivities to serum complement. The present findings suggest that E. coli O157 strains with intermediate or long length Oag chains might show greater resistance to serum complement than those with short chains.